Les normes de la féminité dans la communauté lesbienne [1967] - William Simon; John H. Gagnon (Genre, Sexualité et Société)
A major deficiency in the limited available literature on the female homosexual has been its use of a deviant sexual commitment as a primary explanatory variable. The present paper re-examines selected aspects of both the sexual and non-sexual adaptations of lesbians in terms of general female patterns. Within the limits set by a deviant gender preference, much of the behavior of the lesbian can be explained in terms of non-deviant sex role expectations. The analysis points to the need to consider the lesbian, as well as other deviant actors, in terms not only of the degree of failure of conventional socialization, but also the degree of success of conventional socialization.